Walory poznawcze kategorii tożsamości społecznej jednostki - Machaj, Irena (Człowiek i Społeczeństwo, 2017)
In the article, the author raises the question of what we can get to know or rather what social phenomena we can reach thanks to the studies on the individual’s social identity. The author adopts three essential features of sociological meaning of social identity: concentration on the consciousness part of life, subjective research orientation and the relational character of the individual’s social identity. Cognitive values are presented in the form of explicitly articulated questions, which are posed when we research on the identity of the individual in itself and when it helps to discover the other social phenomena, such as systems of values, mechanisms of the social exclusion-inclusion and mechanisms of the social diversity. Irena Machaj, Walory poznawcze kategorii tożsamości społecznej jednostki [Cognitive values of the category of the individual’s social identity] edited by E. Smolarkiewicz, J. Kubera, „Człowiek i Społeczeństwo” vol. XLIV: Tożsamość i identyfikacje. Propozycje teoretyczne – doświadczenia badawcze [Identity and identifications. Theoretical proposals – research experiences], Poznań 2017, pp. 17-31, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271.